Petrological characteristics of lower Gondwana coal from Singrauli coalfield, Madhya Pradesh, India. (1st January 2014) - Singh, Prakash K.; Singh, Mahendra P.; Volkmann, Norbert; Naik, Amiya S.; Börner, Kristin
This paper entails the results of petrological studies carried out on coal samples drawn from two lower Gondwana coal bearing horizons (Raniganj formation and Barakar formation) of the Singrauli coalfield, Son basin. It emerges from this study that the coals of this basin are banded in nature and are dominated by 'banded dull' and 'dull' components. Further, vitrinite and inertinite are the dominant maceral groups while the macerals of liptinite group occur in relatively low concentration. Chemically, the coals are high in volatile matter and ash contents. The study further reveals that the Jhingurdah top seam of Raniganj formation characteristically has elevated concentration of detrital macerals when compared with the coals of Purewa top, Purewa bottom and Turra seams of Barakar formation. Furthermore, it is evolved that these coals have been generated under a fluvio-lacustrine setting, largely from forest swamp, where an alternate oxic to mildly anoxic moor conditions prevailed.